The role and importance of towns in rebellions against Otto I - Sochacki, Jarosław (City and War, 2021)
During his reign Otto I had to face three serious revolts against his rule, which were initiated by his brothers Thankmar and Henry as well as by his son Liudolf. The aim of this paper is to show the role and importance of towns in these armed riots based upon the analysis of sources mainly of narrative character. The research has concluded that fortified outposts of any kind were of great importance as they allowed a major strengthening of one’ position in particular region. With regard to Thankmar, such role had fallen to such places as Eresburg and Laёr, whose surrender meant the effective end of rebellion. It was similar in other cases during Henry’s rebellion, when fighting was concentrated around Merseburg, Chevermont and Scheidungen, and in the case of Liudolf for whom Regensburg finally became the central point of resistance. In the last case of rebellion an important role was also taken up by such towns as Mainz, Köln, Augsburg and Schwabmünchen in Swabia.